Restitution and the politics of repair tropes, imaginaries, theory - Żółkoś, Magdalena (Edinburgh University Press, 2020)
This book takes a unique approach grounded in political and cultural discourse to develop a political theory of restitution. Challenging assumptions about restitution in the Western legal and political tradition, where it has become nearly synonymous with reacquisition and where legal studies focus on material objects and claims to their ownership, Zolkos argues that the development of restitutive norms has been auxiliary to the emergence of modern state sovereignty, and excavates the restitutive tradition's mythical-religious substrate. Bringing together texts from within and outwith the Western canon of political theory and philosophy, including the writings of Grotius, Durkheim, Freud, and Klein, as well as Mary Shelley's Frankenstein, the book undertakes a dual task: reading literary texts as a political theorising of restitution, and reading political or sociological texts as literary narratives with distinctive 'restitutive tropes' of repair, undoing and return.